The Importance of Self-Control in Financial Management for the Future of Kindergarten Students : Pentingnya Pengendalian Diri Dalam Pengelolaan Keuangan Bagi Masa Depan Pada Siswa Taman Kanak - Kanak - Alexander, Gloria; Tetimau, Felicia Edlyn; Linawati, Nanik (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
Self-control in managing money is very important in life. Knowledge and skills about finance need to be instilled as early as possible to form positive behavior in the future. Therefore, one of the efforts made to instill this attitude in children is by carrying out community service activities. This community service activity was carried out by Petra Christian University students by teaching children at Petra Christian Kindergarten 9. There were various forms of activities carried out. Some of them are puppet shows, coloring, singing together, and decorating piggy banks. The purpose of these activities are to increase children's understanding of the importance of financial management, hone their creativity, and encourage frugal living habits. It is hoped that this community service activity will create better awareness about financial management among the Alpha generation, as well as prepare them for a financially stable future. Abstrak Pengendalian diri dalam mengelola keuangan merupakan hal yang sangat penting dalam kehidupan. Pengetahuan dan keterampilan dalam mengelola keuangan ini perlu ditanamkan sedini mungkin untuk membentuk perilaku yang positif di masa depan. Oleh karena itu, salah satu upaya yang dilakukan untuk menanamkan sikap ini pada anak-anak, adalah dengan melakukan kegiatan pengabdian masyarakat. Kegiatan pengabdian masyarakat ini dilakukan oleh mahasiswa-mahasiswa Universitas Kristen Petra dengan mengajar anak-anak di TK Kristen Petra 9. Bentuk kegiatan yang dilakukan ada bermacam-macam. Beberapa diantaranya adalah pertunjukan boneka, mewarnai, menyanyi bersama, serta menghias celengan. Tujuannya adalah untuk meningkatkan pemahaman anak-anak tentang pentingnya pengelolaan keuangan, mengasah kreativitas mereka, dan mendorong kebiasaan hidup hemat. Dari kegiatan pengabdian masyarakat ini, diharapkan akan menciptakan kesadaran yang lebih baik tentang pengelolaan keuangan di kalangan generasi Alpha, serta mempersiapkan mereka untuk masa depan yang stabil secara finansial.